2022
DOI: 10.1002/btm2.10372
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional morphological revealing of human placental villi with common obstetric complications via optical coherence tomography

Abstract: Placental villi play a vital role in human fetal development, acting as the bridge of material exchange between the maternal and fetal. The abnormal morphology of placental villi is closely related to placental circulation disorder and pregnancy complications. Revealing placental villi three‐dimensional (3D) morphology of common obstetric complications and healthy pregnancies provides a new perspective for studying the role of the placenta and its villi in the development of pregnancy diseases. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…The transverse diameter of the terminal villi and the transverse diameter of the terminal villous capillaries were considerably smaller in group B pre-eclamptic placentae than in group A control placentae in the current study. As per documented data, the majority of the morphological alterations in the placenta in pre-eclampsia may be caused by decreased uteroplacental blood flow, which also accounts for the patho-physiological changes in internal components of the placenta (18,19). Studies have reported that the transverse diameter of terminal villi and terminal villous capillaries were significantly smaller in the pre-elamptic group than in the control group which is in parallel to current research (20,21).…”
Section: Discussionsupporting
confidence: 81%
“…The transverse diameter of the terminal villi and the transverse diameter of the terminal villous capillaries were considerably smaller in group B pre-eclamptic placentae than in group A control placentae in the current study. As per documented data, the majority of the morphological alterations in the placenta in pre-eclampsia may be caused by decreased uteroplacental blood flow, which also accounts for the patho-physiological changes in internal components of the placenta (18,19). Studies have reported that the transverse diameter of terminal villi and terminal villous capillaries were significantly smaller in the pre-elamptic group than in the control group which is in parallel to current research (20,21).…”
Section: Discussionsupporting
confidence: 81%
“…Cardiac optogenetics refers to the delivery of lightsensitive proteins (opsin) to excitable heart tissue to achieve optical regulation of cardiac electrophysiological function, such as non-invasively controlling the heart rhythm [10][11][12]. Meanwhile, optical coherence tomography (OCT), a burgeoning imaging technology in the biomedicine field [13], has also been used in heart function studies based on the Drosophila model. OCT can achieve the noninvasively cross-sectional and 3D visualization of bio-tissue internal structures, with high resolution and imaging speed [14][15][16].…”
Section: Introductionmentioning
confidence: 99%